Effect of Chemical Composition on Martensitic Transformation and Abrasive Wear Resistance of Hadfield Steel - AYADI, Souad; HADJI, Ali (University of Eloued جامعة الوادي, 2018)
In this study, the effect of (Cr+Nb) inoculated Hadfield steel on martensitic transformation and abrasive wear resistance was investigated and compared to standard Hadfield steel. Studied steels were melted in an electric arc furnace. Then, samples were subjected to two solution treatment, at 1080°C then at 1100°C. Optical microscopy (OM), scanning electron microscopy (SEM) and X-ray diffraction (XRD) were performed to estimate the microstructural changes after inoculation and heat treatment. Hardness measurements and abrasive wear tests were also performed to determine the wear behavior of the experimental steels. The results showed that the increasing of Cr+Nb increase the martensitic transformation which improves the hardness and the abrasive wear resistance of Hadfield steel.
International Symposium on Mechatronics and Renewable Energies El-Oued 10- 11 December 2018
Keywords: Hadfield steel, chemical composition, heat treatment, martensitic transformation, abrasive wear resistance